Inovasi Bentuk Penilaian Tes Kompetensi Reseptif Berbahasa Arab dalam Buku Al-'Arabiyah Lin Nasyi'iin Jilid 1 - Yuli Imawan (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
The purpose of conducting this scientific study is to analyze the form of assessment in the book Al Arabiyah Linnasyiin Volume 1 and then provide innovation based on the form of a receptive Arabic competency test, which consists of listening and reading skills. This research was studied using qualitative methods with library research in collecting data. Primary data comes from the book Al Arabiyah Linnasyiin Volume 1, while secondary data comes from books, journal articles and library documents that are relevant to the research. The analysis shows that the results of the receptive competency test in the book are in the form of an objective test. Various forms of objective tests in the book Al Arabiyah Linnasyiin Volume 1 to assess testee's receptive language competence include listening skills; consists of sound imitation tests (pronunciation of letters, words and sentences), and essay tests. While on reading skills; consists of a pronunciation test (letters, words and sentences), an answer-choosing test (true-false and multiple choice) and an essay test. The innovations in the form of listening skill tests include; tests for choosing true-false answers, multiple choice, matching and filling in the blanks, and on reading skills the test for choosing answers can be completed by composing words or sentences and filling in the blanks with words or numbers.